Accounts and balance sheet of Hull Whale Fishery Company, 1754–1757. (27th March 2014) - Stonehouse, Bernard
ABSTRACT: A recently-discovered financial balance sheet, accounting for the first four years' transactions of the Hull Whale Fishery Company (1754–1757), adds detail to present knowledge of British Arctic whaling economics during the early years of the industry. This article summarises previously-known information on the Company and its four ships, and provides transcripts of the balance sheet covering the profits and losses of the early voyages. Based on tabulated details from the transcripts, and additional data from Customs records and muster rolls, it discusses ships, crews, voyages, catches and expenses, the products of oil and baleen, and the profits derived from them. It makes brief comparisons with similar data from Bristol and Exeter in the formative years of the industry, and draws attention to the key significance of the 40 shilling (£2) bounty during the early years.